Adaptive beamforming for photoacoustic imaging using linear array transducer - Suhyun Park; Karpiouk, A.B.; Aglyamov, S.R.; Emelianov, S.Y. (2008 IEEE Ultrasonics Symposium, 2008)
Photoacoustic signals, detected by a transducer array, need to be beamformed for subsequent use in a limited view angle tomography such as B-scan imaging. In the presence of the light scattering or phase aberration, the spatial resolution and contrast in the photoacoustic images are degraded. Phase aberration due to tissues with inhomogeneous acoustic speeds is a major source for image degradation. However, a constant speed of sound (e.g., 1540 m/s) is typically assumed in photoacoustic imaging. Such an assumption can affect the quality of photoacoustic image since changes in sound velocity cause significant phase errors in beamforming. An adaptive weighting method such as coherence factor (CF) technique can improve the ultrasound and photoacoustic image quality significantly. In addition, photoacoustic images can be further improved by applying adaptive beamforming techniques developed for ultrasound imaging. In this study, an adaptive photoacoustic image reconstruction technique that combines an adaptive weighting factor (CF) and an adaptive apodization called minimum variance method (MV) is introduced. Although MV method calculates the optimal apodization weighting factors which minimize the variance of the beamformed signal, it can lead to unexpected weighting factors since it is data dependant. In this case, CF weighting can help to avoid this problem by weighting the output from the MV method based on signal coherence. Simulations were performed to analyze the spatial resolution using a point targets and to demonstrate improvement in phase aberration correction. Numerical studies demonstrated the superior performance of MV adaptive method combined with CF weighting.